Bank Branch Closure Assessment Using DEA - Parsaulian, Renata; Chalid, Dony Abdul (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
The downward trend in the number of commercial bank offices is driven by the bank's efforts to shift banking transactions from physical branch to digital channels in order to improve efficiency. In prioritizing the branch closure, bank needs to define the appropriate method used in the analysis. This case study is intended to identify the parameter to determine the prioritization of bank branch office closure. This study uses a non-parametric approach of Data Envelopment Analysis (DEA) to examine the efficiency and productivity change of branch offices at one of the large bank in Indonesia. The one-stage DEA was used to generate the relative efficiency score, and the input-oriented Variable Return to Scale (VRS) assumption is adopted in data analysis based on the production approach. The Malmquist Productivity Index was also adopted to measure the total factor productivity change. The DEA result shows that a number of closed branches in 2019 and 2020 were actually considered efficient, with increasing productivity, compared to many other inefficient branches. The efficiency and productivity score can be further used by the bank’s management to evaluate the upcoming branch closure as well as the overall branches efficiency.